Risk Factors for and Outcomes of Intraoperative Blood Loss in Liver Resection for Hepatocellular Tumors. Issue 3 (March 2021) - Imai, Daisuke; Maeda, Takashi; Wang, Huanlin; Shimagaki, Tomonari; Sanefuji, Kensaku; Kayashima, Hiroto; Tsutsui, Shinichi; Matsuda, Hiroyuki; Yoshizumi, Tomoharu; Mori, Masaki
Intraoperative blood loss (IBL) during liver resection is a predictor of morbidity, mortality, and tumor recurrence after hepatectomy; however, there have been few reports on patient factors associated with increased IBL. We enrolled consecutive patients who underwent liver resection for primary liver malignancies, and evaluated the predictors of IBL using a data set in which factors that might influence IBL, such as surgical devices, methods and anesthetic technique, were all standardized. We studied 244 patients. A multivariate analysis revealed that higher IBL was an independent risk factor for post-hepatectomy liver failure grade ≥B and overall survival. Multiple linear regression analyses showed serum creatinine, clinically significant portal hypertension (CSPH), tumor size, and major hepatectomy were all significant predictors of IBL. In conclusion, higher IBL was significantly associated with increased morbidity and mortality in patients with primary HCC who underwent liver resection. The risk of IBL was related to several factors including tumor size, serum creatinine, CSPH, and major hepatectomy.